Respuesta :

Answer:

[tex]Y=0.4X^2-2.4X+7.6[/tex]

Step-by-step explanation:

Given:

The quadratic equation in vertex form is given as:

[tex]Y=0.4(X-3)^2+4[/tex]

The standard form of a quadratic equation is:

[tex]y=ax^2+bx+c[/tex]

Now, in order to convert the given equation into standard form, we have to expand [tex](X-3)^2[/tex] using the binomial expansion given by:

[tex](a-b)^2=a^2+b^2-2ab[/tex]

Here, [tex]a=X\ and\ b= 3[/tex]

Therefore,

[tex](X-3)^2=X^2+3^2-2(X)(3)\\(X-3)^2=X^2+9-6X[/tex]

Now, plug in this expanded form into the original equation. This gives,

[tex]Y=0.4(X^2+9-6X)+4[/tex]

Now, we use distribute 0.4 inside the parenthesis. This gives,

[tex]Y=0.4X^2+(0.4\times9)-(6X\times0.4)+4\\Y=0.4X^2+3.6-2.4X+4\\Y=0.4X^2-2.4X+4+3.6\\Y=0.4X^2-2.4X+7.6[/tex]

Therefore, the standard form of the given equation is:

[tex]Y=0.4X^2-2.4X+7.6[/tex]

ACCESS MORE